Analysis of 37 cases of percutaneous balloon compression for primary trigeminal neuralgia: experience and outcome from a single center - Xu, Hui; Wang, Shilong; Wang, Ganggang; Dong, Jiangtao; Xu, Haoxiang; Ma, Wenhua (Frontiers in Surgery, 2025)
ObjectiveThis study investigated the therapeutic effect and clinical experience of percutaneous balloon compression (PBC) for the treatment of primary trigeminal neuralgia (TN).MethodsThis is a retrospective study. We enrolled 37 patients with symptomatic primary unilateral TN who underwent PBC and 217 patients who received microvascular decompression (MVD) at our hospital from May 2020 to May 2023. Data on demographics, surgical techniques, pain relief outcomes, and postoperative complications were collected and analyzed. The pain relief and complications of patients receiving PBC were compared to those of patients with MVD.ResultsFor 37 patients receiving PBC, the mean follow-up time was 12.6 months. Successful treatment was achieved in 35 cases, while 2 cases failed due to foramen ovale stenosis. Among the patients who were successfully treated, all 35 (100%) patients experienced immediate pain relief, and all developed facial numbness immediately following the procedure. At the last follow-up, 11 (31.4%) patients with facial numbness had resolved, and 24 (68.6%) patients had varying degrees of response. Masseter weakness was observed in 23 patients (65.7%), which recovered at 3 months of follow-up. No instances of intracranial hemorrhage, keratitis, diplopia, intracranial infection, or death were reported in this study. A significant association was identified between balloon compression duration, balloon shape, and pain relief outcomes, with approximately 3 min of compression and typical pear-shaped balloons achieving optimal results. Comparatively, PBC demonstrated comparable rates of complete pain relief to MVD, although MVD had lower rates of complications.ConclusionPBC is an effective and safe minimally invasive technique for managing primary TN, demonstrating high rates of immediate pain relief. Despite being associated with transient complications, PBC allows for a rapid recovery and return to normal activities. These findings underscore the need for careful patient selection and consideration of potential postoperative complications when opting for PBC vs. MVD. Further studies should explore long-term outcomes and strategies to minimize complications associated with PBC.